Transcriptomic study on the impact of temporomandibular joint internal derangement in the condylar cartilage of rabbits - Wang, Shuhua (Genom Data, 2015)
Internal derangement (ID) in the temporomandibular joint (TMJ) compromises a group of clinical problems, and holds a relative high prevalence in populations. However, the temporal genomic change in gene expression of condylar cartilage during continuous ID remains unclear. Here we reported the differentially expressed gene pattern in condylar cartilage of rabbits with ID from 1 to 8 weeks by microarray analysis. The whole genome project was deposited at GenBank under the accession PRJNA278127. The microarray analysis showed that 6478 genes have more than two-fold changes among all the tested transcripts. Many inflammation gene increased rapidly in the early stage while decrease later. On the contrary, the bone construction related genes showed a low level at first and increased at later period in the ID progression. Besides, the current study found some genes such as HLA2G, which had never been reported, might be relevant with ID.